Low-Noise Plasmonic Nanopore Biosensors for Single Molecule Detection at Elevated Temperatures - Crick,CR; Albella,P; Kim,H-J; Ivanov,AP; Kim,K-B; Maier,SA; Edel,JB (ACS Photonics, 2017)
Advanced single molecular analysis is a key stepping stone for the rapid sensing and characterization of biomolecules. This will only be made possible through the implementation of versatile platforms, with high sensitivities and the precise control of experimental conditions. The presented work details an advancement of this technology, through the development of a low-noise Pyrex/silicon nitride/gold nanopore platform. The nanopore is surrounded by a plasmonic bullseye structure and provides targeted and controllable heating via laser irradiation, which is directed toward the center of the pore. The device architecture is investigated using multiwavelength laser heating experiments and 'individual DNA molecules are detected under controlled heating. The plasmonic features, optimized through numerical simulations, are tuned to the wavelength of incident light, ensuring a platform that provides substantial heating with high signal-to-noise.